Did a successful fight against COVID-19 come at a cost? Impacts of the pandemic on employment outcomes in Vietnam. (January 2023) - Dang, Hai-Anh H.; Nguyen, Cuong Viet; Carletto, Calogero
Highlights: Vietnam has been widely praised for its success in the fight against early waves of the COVID-19 pandemic. We analyze several rounds of the Vietnam's Labor Force Surveys spanning 2015 to 2020. We find post-pandemic increased unemployment and temporary layoff rates and decreased employment quality. Monthly wages decreased but the proportion of workers receiving below-minimum wages substantially increased, contributing to sharply rising wage inequality. Our findings suggest more resources can be allocated to protect vulnerable workers. Abstract: Despite its low middle-income status, Vietnam has been widely praised for its success in the fight against early waves of the COVID-19 pandemic, with a low mortality rate of approximately 100 deaths out of a population of less than 100 million by the end of 2020. We add to the emerging literature on COVID-19 effects on the labor market for poorer countries by analyzing rich individual-level data from Vietnam's Labor Force Surveys spanning 2015 to 2020. We find post-pandemic increases in unemployment and temporary layoff rates alongside decreases in employment quality. Monthly wages declined even as the proportion of workers receiving below-minimum wages substantially increased, contributing to sharply rising wage inequality. Our findings suggest that more resources should be allocated to protect vulnerable workers, especially as the pandemic continues to cause increasingly severe damage to the global economy.